LANGUAGE STYLE USED IN THE SLOGANS OF INDONESIAN POLITICAL PARTIES 2014 CAMPAIGN ADVERTISEMENTS - WARDHANI, RURIE SETYA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Language style, Diction, Sentence Structure, Social Factors, Indonesian Political Parties, Campaign Slogan.Language style is the way how to use language that can show the user’s characteristics. In order to use language in spoken or written communication, people rather to have their own style. In this study, the writer is interested in investigating the types of language style used in the slogans of Indonesian political parties 2014 campaign advertisements based on the diction, based on the sentence structure and also the social factors. The research problems of the study are : (1) what types of language style are used in the slogan of Indonesian political parties 2014 campaign advertisements based on the diction (2) what types of language style are used in the slogan of Indonesian political parties 2014 campaign advertisements based on the sentence structure (3) what the social factors influence the types of language style used in the slogan of Indonesian political parties 2014 campaign advertisements.This study used qualitative approach. The data were the slogan of Indonesian political parties campaign advertisements. In analyzing t he data, the writer used theories by Keraf (2009), Chaer (2006) and Holmes (2001). There were five Indonesian political parties in this study.The types of language style based on diction that mostly found in the slogans of Indonesian Political Parties campaign advertisement is formal style, followed by informal style and the last is spoken style. While, the types of language style based on sentence structure that mostly found is parallelism style, followed by repetition style and the last style is climax. Regarding the social factors that influence the types of language style used in the slogan, the writer found that function factor is the most dominant factor that influence the slogan. Then the second factor is participants with seven slogans and the third factor is topic and the last factor that influence is setting.In short, the writer finds the type of language style used in the slogan of campaign advertisements based on its diction and sentence structure and also the social factors that influence it. The writer suggests that the future writer to find the types of language style in the spoken data so they can analyzed the types of language style based on the tone or meaning. It is also suggested for the future writers to analyze to use another theories beside Keraf and Holmes theory to analyze the language style